Re-evaluating Small and Medium Enterprises financial accessibility post COVID-19 pandemic in Nigeria - Mirhiga Peter Okuwhere; Osagie Osifo (Journal of Enterprise and Development (JED), 2022)
Purpose — This paper re-examined financial accessibility for Small and Medium Enterprises (SMEs) in Nigeria by considering the times we live occasioned by the pandemic.Method — The study adopts the cross-sectional survey research design. The primary data in this study were obtained via a questionnaire administered to 270 SMEs in Abia State, Nigeria, who had applied for credit from a bank within the last two years. The data were collected using a self-administered survey.Result — The study showed that collateral is still a significant determinant of access to credit, as an increase in the ability of SMEs to provide collateral will significantly impact their access to credit. SME size (SSIZE) was found to have a positive and significant effect on credit access, implying that large SMEs are better able to access credit. Though SME age (SAGE) had an insignificant effect on access to credit and Cost of Credit (CCR) was found to impair access to credit which is significant at 5%. This is in line with expectation as a high-interest rate will discourage SMEs from seeking credit from banks. Contribution — This study contributes to the emerging discourse on financial accessibility in Nigeria post COVID-19. It presented a useful insight into how the government, through its fiscal, monetary policy and direct intervention, could play a more active role in helping SMEs bounce back from the challenges brought in by the pandemic.